On modified skew logistic regression model and its applications - C. Satheesh Kumar (Statistica, 2015)
Here we consider a modiﬁed form of the logistic regression model useful for situations where the dependent variable is dichotomous in nature and the explanatory variables exhibit asymmetric and multimodal behaviour. The proposed model has been ﬁtted to some real life data set by using method of maximum likelihood estimation and illustrated its usefulness in certain medical applications.